Supervision in the classroom : a manual - Ghobril, Nicole S (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2005)
The study examines the different types of supervision and provides teachers with opportunities to expand their abilities to provide students with effective and authentic learning. It is conducted through a number of informal interviews with teachers in private schools in Lebanon to obtain information relating to supervisory practices within the country. The study aims to improve supervision in Lebanon and to show how to select the different types of supervision by providing a manual to assist teachers in applying peer coaching as a method of supervision.
: Mémoire
Keywords: Class Management; Gestion d une classe